2014
DOI: 10.3895/s1808-04482013000400005
|View full text |Cite
|
Sign up to set email alerts
|

Lean Service: Aplicação Do Mapeamento Do Fluxo De Valor Em Uma Organização De Serviços

Abstract: ResumoNeste artigo desenvolve-se a aplicação do Mapeamento do Fluxo de Valor (MFV) Palavras-chave: lean service; corretora de seguros; gestão de serviços. IntroduçãoO setor de serviços de seguro é um dos setores que mais tem crescido em termos de concorrência acirrada, aonde a diferenciação dos produtos pode representar significativas vantagens competitivas (ZILBER e BRANCALIÃO, 2008). De fato, o setor é reconhecidamente competitivo, porém a vantagem competitiva pode não estar apenas nos produtos oferecidos.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 6 publications
1
4
0
6
Order By: Relevance
“…It is observed that in this study, as in the researches of Roman et al (2013) and Zanchet et al (2007), the time that does not add value (in its majority, in the form of waiting) is much higher than the time it adds value. These findings reinforce the importance of resuming the value flow mapping goal: to eliminate activities that do not add value, so that the flow of value is increasingly efficient (Hofacker et al, 2012).…”
Section: Map Of Future Value Flowsupporting
confidence: 62%
See 2 more Smart Citations
“…It is observed that in this study, as in the researches of Roman et al (2013) and Zanchet et al (2007), the time that does not add value (in its majority, in the form of waiting) is much higher than the time it adds value. These findings reinforce the importance of resuming the value flow mapping goal: to eliminate activities that do not add value, so that the flow of value is increasingly efficient (Hofacker et al, 2012).…”
Section: Map Of Future Value Flowsupporting
confidence: 62%
“…Similar to the targets of Roman et al (2013) and Zanchet et al (2007), these improvements are intended to make the flow more efficient and, consequently, to increase student satisfaction (customers of this process). This proposal was sent to leaders who, in the collaborator gives the conference of discharge and delivers the document to the student.…”
Section: Map Of Future Value Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Importante mencionar que antes da confecção do MFV, é necessário atentar-se às etapas mencionadas na figura 1 dessa pesquisa. Essa seleção segundo Roman et al (2014) é importante quando há uma grande diversidade de serviços e consequentemente vários fluxos diferentes.…”
Section: Segunda Etapa: Mfv Atual E Cálculo Lead Timeunclassified
“…O lean service é aplicável nos mais variados tipos de empresas, como empresas de serviços de tecnologia da informação (Fortes, 2010), corretoras de seguros (Roman et al, 2013), centros de serviços compartilhados (Sum, 2016), dentre outras. Neste âmbito, identificou-se a oportunidade de aplicação dessa metodologia para a melhoria do processo de serviço de uma empresa júnior de consultoria, definida como uma organização sem fins lucrativos gerida por estudantes de um determinado curso superior.…”
Section: Introductionunclassified